Can words heal? Using affect labeling to reduce the effects of unpleasant cues on symptom reporting - Constantinou, Elena; Van Den Houte, Maaike; Bogaerts, Katleen; Van Diest, Ilse; Van den Bergh, Omer (Frontiers in Psychology, 2014)
Processing unpleasant affective cues induces elevated momentary symptom reports, especially in persons with high levels of symptom reporting in daily life. The present study aimed to examine whether applying an emotion regulation strategy, i.e. affect labeling, can inhibit these emotion influences on symptom reporting. Student participants (N=61) with varying levels of habitual symptom reporting completed six picture viewing trials of homogeneous valence (3 pleasant, 3 unpleasant) under 3 conditions: merely viewing, emotional labeling or content (non-emotional) labeling. Affect ratings and symptom reports were collected after each trial. Participants completed a motor inhibition task and self-control questionnaires as indices of their inhibitory capacities. Heart rate variability was also measured. Labeling, either emotional or non-emotional, significantly reduced experienced affect, as well as the elevated symptoms reports observed after unpleasant picture viewing. These labeling effects became more pronounced with increasing levels of habitual symptom reporting, suggesting a moderating role of the latter variable, but did not correlate with any index of general inhibitory capacity. Our findings suggest that using an emotion regulation strategy, such as labeling emotional stimuli, can reverse the effects of unpleasant stimuli on symptom reporting and that such strategies can be especially beneficial for individuals suffering from medically unexplained physical symptoms.